Implementation evaluation of multiple complex early years interventions: an evaluation framework and study protocol. Issue 1 (20th June 2019) - Dharni, Nimarta; Dickerson, Josie; Willan, Kathryn; Ahern, Sara; Dunn, Abigail; Nielsen, Dea; Uphoff, Eleonora; McEachan, Rosemary R C; Bryant, Maria
Abstract : Introduction: Implementation evaluations are integral to understanding whether, how and why interventions work. However, unpicking the mechanisms of complex interventions is often challenging in usual service settings where multiple services are delivered concurrently. Furthermore, many locally developed and/or adapted interventions have not undergone any evaluation, thus limiting the evidence base available. Born in Bradford's Better Start cohort is evaluating the impact of multiple early life interventions being delivered as part of the Big Lottery Fund's 'A Better Start' programme to improve the health and well-being of children living in one of the most socially and ethnically diverse areas of the UK. In this paper, we outline our evaluation framework and protocol for embedding pragmatic implementation evaluation across multiple early years interventions and services. Methods and analysis: The evaluation framework is based on a modified version of The Conceptual Framework for Implementation Fidelity. Using qualitative and quantitative methods, our evaluation framework incorporates semistructured interviews, focus groups, routinely collected data and questionnaires. We will explore factors related to content, delivery and reach of interventions at both individual and wider community levels. Potential moderating factors impacting intervention success such as participants' satisfaction, strategies to facilitate implementation, quality of delivery and context will also be examined. Interview and focus guides will be based on the Theoretical Domains Framework to further explore the barriers and facilitators of implementation. Descriptive statistics will be employed to analyse the routinely collected quantitative data and thematic analysis will be used to analyse qualitative data. Ethics and dissemination: The Health Research Authority (HRA) has confirmed our implementation evaluations do not require review by an NHS Research Ethics Committee (HRA decision 60/88/81). Findings will be shared widely to aid commissioning decisions and will also be disseminated through peer-reviewed journals, summary reports, conferences and community newsletters.